Hubungan Pola Konsumsi Pangan dengan Kadar Hemoglobin pada Ibu Hamil Trimester Ketiga di Wilayah Kerja Puskesmas Desa Lalang Kecamatan Medan Sunggal Tahun 2013 - Marissa Anggraini; Evawany Y Aritonang; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Food consumption pattern is a description of the quantity , type and frequency of food that people eat everyday and it is typical to one particular group of people. The research objective was to determine the relationship of the pattern of food consumption with haemoglobin levels in pregnant mother in the third trimester in Desa Lalang Health Center in Medan Sunggal SubDistrict in 2013. This type of research is an observational cross-sectional design. The population is all pregnant mother with gestational age 27-40 weeks ( third trimester ) who reside in the Desa Lalang Health Center as many as 70 people. The samples are randomly by 50 people. The results showed that mothers who have normal haemoglobin levels are 40.0 % and 60.0 % are anemia . There are significant relationship between energy sufficiency, the adequacy of protein , the adequacy of iron , the adequacy of folic acid and iron supplement tablets with hemoglobin levels in pregnant mother in the third trimester Desa Lalang Health Center in Medan Sunggal SubDistrict in 2013. In other hand there was no relationship between the adequacy of vitamin B12 with the levels of hemoglobin in the third trimester pregnant mother. It is recommended to pregnant mother to pay attention to the pattern of food consumption and nutrition supplements of iron tablets during pregnancy to prevent anemia in pregnant mother in the third trimester that affecting mother and fetus. Desa Lalang Health Center in Medan Sunggal SubDistrict need to improve health care and provide information to pregnant mother in hopes of improving the welfare of mother and child as the nation's resource development. Keywords : Haemoglobin Levels, Food Consumption Pattern, Pregnant Mother, Third Trimester